The Effect of the Utilization of Fermented Tofu Waste Products on Hatching Rate and Survival Rate of Climbing Perch (Anabas testudineus) - Hisra Melati; Fakhrunnas MA Jabbar; Safitriani Safitriani (Jurnal Natur Indonesia, 2024)
Climbing perch (Anabas testudineus) is a type of swamp fish that has the potential to be cultivated. The obstacle faced in developing climbing perch cultivation is that the eggs produced are very few and vulnerable to inorganic substances or waste because it takes quite a long time to reach seed size. Climbing perch usually food aquatic plants such as kiambang, weeds, and other small animals and insects. It analyzes the effect of various concentrations of tofu liquid waste on the transparent hatchability and survival of climbing perch larvae and the use of research results on the influence of various concentrations of tofu liquid waste on the transparent hatchability and survival of climbing perch fish larvae. A 100% concentration of tofu liquid waste produced the highest survival in the P4 treatment (64.00%), and the lowest concentration without giving tofu liquid waste concentration at P0 was (40.00%). A 100% concentration of tofu liquid waste produced the highest hatchability in the P4 treatment ( 60.00 %), and the lowest concentration without providing tofu liquid waste at P0 was (42.00 %). The research fulfilled the maintenance requirements by utilizing fermented tofu liquid waste as a medium for rearing climbing perch eggs and larvae. It is not possible to use 100% tofu liquid waste for climbing perch, and it is not possible to use 100% tofu liquid waste for climbing perch larvae in the long term